Time trends (2006–2015) of quality indicators in EUSOMA-certified breast centres. (November 2017) - ; Badbanchi, F.; Catalano, G.; Cretella, E.; Daniaux, M.; Emons, A.; van Eygen, K.; Ettl, J.; Gatzemeier, W.; Kern, P.; Schneeweiss, A.; Stoeblen, F.; et al.
Abstract: Aim of the study: The European Society of Breast Cancer Specialists (EUSOMA) has fostered a voluntary certification process for breast centres to establish minimum standards and ensure specialist multidisciplinary care. Prospectively collected anonymous information on primary breast cancer cases diagnosed and treated in the units is transferred annually to a central EUSOMA data warehouse for continuous monitoring of quality indicators (QIs) to improve quality of care. Units have to comply with the EUSOMA Breast Centre guidelines and are audited by peers. The database was started in 2006 and includes over 110, 000 cancers from breast centres located in Germany, Switzerland, Belgium, Austria, The Netherlands, Spain, Portugal and Italy. The aim of the present study is assessing time trends of QIs in EUSOMA-certified breast centres over the decade 2006–2015. Materials and methods: Previously defined QIs were calculated for 22 EUSOMA-certified breast centres (46122 patients) during 2006–2015. Results: On the average of all units, the minimum standard of care was achieved in 8 of 13 main EUSOMA QIs in 2006 and in all in 2015. All QIs, except removal of at least 10 lymph nodes at axillary clearance and oestrogen receptor–negative tumours (T > 1 cm or N+) receiving adjuvant chemotherapy, improved significantly in this period. The desirable target was reached for two QIs in 2006 and for 7 of 13 QIs in 2015. Conclusion: The EUSOMA model of audit and monitoring QIs functions well in different European health systems and results in better performance of QIs over the last decade. QIs should be evaluated and adapted on a regular basis, as guidelines change over time. Highlights: The time trends of quality indicators in EUSOMA-certified breast centres over the decade 2006–2015 are evaluated. The EUSOMA model of audit and monitoring QIs functions well in different European health systems. Audit and measuring quality indicators result in better performance.